The Routine Use and Cost Analysis of Acid-Fast Bacilli and Fungal Cultures in Foot and Ankle Surgery: A Retrospective Study. Issue 1 (January 2022) - El-Zein, Zein S.; Diamond, Scott; Bohr, Margaret; Baker, Erin A.; Fleischer, Mackenzie M.; Gehrke, Corinn; Fortin, Paul T.; Vaupel, Zachary M.
Category: Other; Diabetes Introduction/Purpose: Infections pertaining to orthopaedic surgery play a major role in patient morbidity and increased healthcare-associated expenses. In the setting of foot and ankle surgery for infection, it is common practice to send acid-fast bacilli (AFB) and fungal intraoperative cultures, although there is no standard protocol in place. In this study, the rate of positive AFB and fungal cultures and associated costs in a consecutive series of foot and ankle surgeries was retrospectively assessed. Methods: Under an IRB-approved protocol, CPT codes were used to identify 447 procedures in 320 patients, who underwent foot and ankle surgery for infection by fellowship-trained foot and ankle orthopaedic surgeons at a Level 1, private, academic hospital from 2014 to 2019. A medical records review was performed to collect microbiology and patient demographic data. Materials and labor cost data, which was provided by the institution, was used to quantify a total culture cost. Results: In this series, there were 185 male and 135 female patients with an average age of 57 years (range, 10-105) and average BMI of 31 kg/m 2 (range, 13-56). No patients had positive AFB cultures and 20 patients (7.5%) had positive fungal cultures. There were 434 AFB and 525 fungal cultures performed during these procedures. Based on total cultures performed, there were 0% (0/434) AFB and 5% (26/525) fungal culture positivity rates. The total intra-institutional cost (i.e. labor and materials) for AFB cultures was $23, 967. The total labor/materials cost for negative and positive fungal cultures was $12, 428 and $2, 371, respectively. The total labor/materials cost for all the cultures obtained over the time frame of our study was $38, 767. Conclusion: This study highlighted low rates of positive AFB and fungal cultures in the orthopaedic foot and ankle surgery service in a 6-year retrospective review, as well as substantial institutional costs of routine use of intraoperative cultures. While this series included cases from three fellowship-trained foot and ankle orthopaedic surgeons, this study will be expanded to analyze AFB and fungal culturing practices and cost in other orthopaedic subspecialties. Creating and implementing a standardized protocol may achieve cost effectiveness of cultures without diminishing patient outcomes.